Chinese Learning as a Second Language for Kindergarten Students in Makassar - Mir'ah Azizah (Universitas Negeri Makassar, 2023)
Abstract. This research was conducted at Makassar International School (MIS) Kindergarten in Makassar City by observing Chinese learning activities using a descriptive-analytical approach. To obtain valid data, researchers used several data collection techniques such as interviews, analysis of Daily Learning Implementation Plan documents made by the teacher, and class observations when giving Chinese content to Early Childhood Learners. The final results of this study revealed that the provision of Chinese content for MIS Kindergarten students was carried out by inserting Chinese utterances or vocabulary into the learning process and the process of interaction at school associated with the theme of learning every day. This supports the theory of language acquisition put forward by Chomsky said that the acquisition of a second language (L2/Second Language) should be carried out as a first language (L1/First Language) is obtained, namely in the most scientific way possible by using simple utterances in accordance with the context of everyday life. Keywords: Chinese Learning, early childhood, Second Language Acquisition